Tit for Tat in the Dear Enemy Relationship Between Territorial Females of a Cichlid Fish - Sogawa, Shumpei; Kohda, Masanori (Frontiers in Ecology and Evolution, 2018)
Many territorial animals reduce aggression toward their neighbours once territorial boundaries are established. This relationship is called the dear enemy phenomenon, hypothetically based on a conditional strategy like tit for tat (TFT). However, studies on territorial animals such as male songbirds do not fully support this hypothesis. We tested the TFT hypothesis in females of the territorial cichlid Neolamprologus pulcher, which exhibits dear enemy relationships, under laboratory conditions. Focal fish attacked invading neighbours as frequently as invading strangers, but they immediately stopped attacking the dear neighbour after the neighbour returned to its own territory, whereas they kept attacking strangers even after they stopped invading. These responses of territory owners are consistent with the predictions of TFT theory. Interestingly, fish were likely to remain vigilant toward the neighbour after its invasion and subsequent return to its own territory.